Local estrogens administration - Baranowski, Włodzimierz (Menopause Review/Przegląd Menopauzalny, 2006)
Updated data on topical oestrogen treatment are presented. Basic molecular mechanisms (receptor and extrareceptor activities) of oestrogens action, particularly in local (urogyneacological) treatment are described. Current papers on indications, contraindications, advantages and disadvantages, different treatment regimens, as well as different medical formulas of oestrogens are reviewed